2018
DOI: 10.1002/nop2.137
|View full text |Cite
|
Sign up to set email alerts
|

Living condition, weight loss and cognitive decline among people with dementia

Abstract: AimsThe aim of this study was to investigate cognitive performance and BMI of patients with dementia living in their own homes with family members, nursing homes and alone.DesignA prospective observational cohort study with a quantitative design.MethodMini–mental state examination (MMSE) scores and BMI were examined with a sample of Slovak patients (N = 428). Patients were followed up 12 months later after the first examination.ResultsCognitive decline was significantly faster for patients living in nursing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Fifthly, institutionalized seniors may be subject to other important factors, physical or psychological, connected with living in a NH that influence the development of depression, dementia or functional decline. Living in a NH and its associated social isolation both anticipate progress in dementia [ 56 ]. Isolation and loneliness are also associated with a rapid rate of motor decline [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifthly, institutionalized seniors may be subject to other important factors, physical or psychological, connected with living in a NH that influence the development of depression, dementia or functional decline. Living in a NH and its associated social isolation both anticipate progress in dementia [ 56 ]. Isolation and loneliness are also associated with a rapid rate of motor decline [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed similar cognitive impairment in older adults living in LTCFs and patients with AD, suggesting that elderly individuals in LTCF have a high risk of dementia, although few screening psychiatric evaluations are implemented, leading to underdiagnosis in this population. Several studies have shown a cognitive decline in institutionalized elderly individuals [3][4][5][6][7] , and the hospitalization and social isolation have also been shown to have significant impacts 23 . Among other factors, the increased sedentary behaviour correlates with motor and cognitive decline in this population 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that who have become institutionalized present more cognitive decline than those who remain in the community [4][5][6] . Institutionalization leads to a reduction in the motor demands inherent in social life and shows an important relationship with the decrease in cognitive abilities 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The Urban Benchmarking Tool and the CityBench Tool are widely used in Europe [28,29]. Some other experts and scholars have also carried out some relevant research works [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%